Psychological risk factors that characterize acute stress disorder and trajectories of posttraumatic stress disorder after injury: a study using latent class analysis. Issue 1 (31st December 2022) - Visser, Eva; Den Oudsten, Brenda Leontine; Lodder, Paul; Gosens, Taco; De Vries, Jolanda
ABSTRACT: Background: The course and different characteristics of acute and posttraumatic stress disorder (ASD, PTSD) in trauma populations are unclear. Objective: The aims were to identify longitudinal trajectories of PTSD, to establish a risk profile for ASD and PTSD based on patients' sociodemographic, clinical, and psychological characteristics, and to study the effect of ASD and dissociation on PTSD during 12 months after trauma. Method: Patients completed questionnaires after inclusion and at 3, 6, 9, and 12 months afterwards. Trajectories were identified using repeated measures latent class analysis (RMLCA). The risk profile was based on a ranking of importance of each characteristic using Cohen's d effect sizes and odds ratios. The impact of ASD and dissociation on PTSD was examined using logistic regression analyses. Results: Altogether, 267 patients were included. The mean age was 54.0 ( SD  = 16.1) and 62% were men. The prevalence rate of ASD was approximately 21.7% at baseline, and 36.1% of trauma patients exhibited PTSD at 12 months after injury. Five trajectories were identified: (1) no PTSD symptoms, (2) mild, (3) moderate, (4) subclinical, and (5) severe PTSD symptoms. These trajectories seemed to remain stable over time. Compared with patients in other trajectories, patients with ASD and (subclinical) PTSD were younger and scored higher on anxiety, depressive symptoms, neuroticism, and trait anxiety. Regarding dissociation symptoms, inability to recall memories about the event was significantly more present than an altered sense of reality, (105 (40.7%) versus 56 (21.7%), p = .031), although that symptom had the strongest likelihood for PTSD. Patients with dissociation were significantly at risk for PTSD than patients without dissociation (OR = 4.82; 95%CI: 1.91–12.25). Conclusions: Psychological factors characterized ASD and trajectories of PTSD during 12 months post-trauma. Healthcare providers who are aware of these findings could early identify patients at risk for ASD and PTSD and refer them for patient-centred interventions. HIGHLIGHTS: Longitudinal trajectories of posttraumatic stress disorder (PTSD) after physical trauma were evaluated. A risk profile for ASD and PTSD was subsequently determined. Overall, only psychological characteristics determined ASD and PTSD. No clinical characteristics were found.